2022
DOI: 10.1371/journal.pone.0277712
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in airflow characteristics and effect on the NOSE score after septoturbinoplasty: A computational fluid dynamics analysis

Abstract: Septoturbinoplasty is a surgical procedure that can improve nasal congestion symptoms in patients with nasal septal deviation and inferior turbinate hypertrophy. However, it is unclear which physical domains of nasal airflow after septoturbinoplasty are related to symptomatic improvement. This work employs computational fluid dynamics modeling to identify the physical variables and domains associated with symptomatic improvement. Sixteen numerical models were generated using eight patients’ pre- and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Another study showed that the nasal valve volume and angle were increased using magnetic resonance imaging [49]. In addition, a computational fluid dynamics study comparing nasal resistance and airflow changes before and after septal surgery decreased total nasal resistance after surgery by 50% compared to before surgery [50]. Based on these study results, nasal surgery has been shown to address nasal obstruction in patients wi effectively the OSA.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
“…Another study showed that the nasal valve volume and angle were increased using magnetic resonance imaging [49]. In addition, a computational fluid dynamics study comparing nasal resistance and airflow changes before and after septal surgery decreased total nasal resistance after surgery by 50% compared to before surgery [50]. Based on these study results, nasal surgery has been shown to address nasal obstruction in patients wi effectively the OSA.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
“…Sinonasal pathologies, such has nasal polyposis and inverted papilloma have been shown to negatively affect OSA and CPAP compliance necessitating adequate disease control in order to improve OSA [30][31][32]33 & ] Surgical correction of nasal obstruction often involves septoplasty, inferior turbinate reduction, and/or internal nasal valve repair. Additionally, in patients with chronic rhinosinusitis, endoscopic sinus surgery can improve mucosal inflammation causing nasal obstruction [34]. The literature has also revealed that nasal surgery in OSA patients can positively impact PAP compliance [35].…”
Section: Key Pointsmentioning
confidence: 99%
“…This is thought to be because less PAP pressure is required for maintaining airway patency [35]. In a study evaluating flow dynamics before and after septal surgery, there was also a 50% decrease in total nasal resistance postoperatively [34]. In doing so, nasal surgery helps mitigate the negative pressure gradient that promotes pharyngeal collapse in OSA.…”
Section: Nasal Airwaymentioning
confidence: 99%
“…Additional advances in airflow engineering enhance aerosol and particulate containment, strengthening infection control methods. Non-technological research can produce innovative filters with greater efficiency, capable of capturing tiny particles and bacteria [61].…”
Section: Airflow Engineering and Innovative Filtersmentioning
confidence: 99%
“…Additional advances in airflow engineering can result in more effective aerosol and particulate containment, strengthening infection control methods. Innovative filters with even greater efficiency, capable of capturing tiny particles and bacteria, may be produced by non-technological research [ 61 ]. Data tracking, remote monitoring, and automatic maintenance planning could all be made possible with the integration of BSCs with laboratory information systems.…”
Section: Reviewmentioning
confidence: 99%